Differential Equations of Motion of the Particle - Karn, Uday Kumar; Karna, Sushil Chandra (Orchid Academia Siraha, 2022)
This paper deals with linearized and normalized differential equations of relative motion of the system under the influence of magnetic force air resistance and oblateness of the earth in Nechvill's co-ordinate system. We have linearized the problem keeping in view that the length of the string connecting the two satellites is infinitesimally small in comparison to the distance of centre of mass of the system from the centre of attracting force and introduction of rotating frame of reference eliminates the product terms as usual. We have obtained a system of six orders non-autonomous, non-linear equations of motion describe the motion of one of two satellites and the motion of satellite relative to the first may easily be obtained by m1ρ1 + m2ρ2 = 0